PERFORMANCE OF THE FREQUENCY-RESPONSE-SHAPED LMS ALGORITHM IN IMPULSIVE NOISE - Ahmad, Mohammad Shukri; Hocanin, Aykut; Kukrer, Osman (IEEE, 2007)
The performance of the Frequency-Response-Shaped Least Mean Square (FRS-LMS) adaptive algorithm in estimating a sinusoidal signal in impulsive and correlated noise is investigated. The algorithm does not require a priori knowledge about the nominal Gaussian process and is able to adapt to changes in the environment. The performance of the FRS-LMS is compared to that of the Leaky-LMS algorithms in terms of Mean Square Error (MSE) and convergence speed. The results indicate that while the FRS-LMS and the Leaky LMS algorithms perform similarly in AWGN, the FRS-LMS provides superior performance in impulsive and correlated noise environments. The performance gain is due to the frequency shaping and outlier reduction properties of the algorithm.
IEEE International Conference on Signal Processing and Communications -- NOV 24-27, 2007 -- Dubai, U ARAB EMIRATES
Keywords: FRS-LMS; Leaky-LMS; correlated noise; impulsive noise